Permanent establishment as a foreign direct investment in Poland: Identification of tax barriers in the context of new tax development - Marcin Jamroży; Magdalena Janiszewska (International Journal of Management and Economics, 2021)
The paper aims to identify the significant tax barriers to foreign direct investment (FDI) in Poland, in particular in the form of a permanent establishment (PE), in the context of new developments in international tax law. Due to the recommendations of the Base Erosion and Profit Shifting (BEPS) project, launched by Organisation for Economic Co-operation and Development (OECD) to prevent international tax avoidance, the understanding of PE has changed, which could lead to changes in business models. The purpose of the research is also to identify the significant tax barriers to economic activity in Poland, in particular in the form of PE, against the international tax law context. The study conducted by the authors relies on the most current tax rulings and judgments of administrative courts issued between 2017 and 2020. It is concluded that not so much the effective tax burdens but the regulatory ambiguity surrounding the tax obligations may contribute to the reduction of Poland's attractiveness as a location for FDI.
Keywords: F65; F21; H26; K34; 650; BEPS; foreign direct investment; permanent establishment